Profil Kesegaran Jasmani Siswa Putra Kelas X SMK N Jateng Di Semarang - Umarul Syifa; Endang Sri Hanani (Universitas Negeri Semarang, 2024)
Physical Freshness is a person's ability to do a variety of activities but not feel fatigue that is so meaningful to him. Daily activities at SMK N Central Java can be categorized as very dense. For the initial activity, all students, both grades X, XI, and XII, are required to wake up at 03.00 am to perform the tahajud prayer, followed by the Qur'an tadabbur. At 04.30 dawn prayer in congregation, run in the morning and after that return to the dormitory to clean up and continued at 06.00-07.00 in the morning and continued learning or KBM. This makes many students feel tired with so many activities at school. The research method used is a Survey with a type of Descriptive Quantitative research. The determination in the author's sample, using the census/total sampling technique, with the number of students 87. Data collection technique using 5 physical fitness test instruments aged 16-19 years namely running 60 meters, hanging body lifts, sitting down, jumping upright, and running 1200 meters. The results of the research conducted by the author showed thatthe students of SMK N Central Java in Semarang were categorized as very good 0%, categorized as good 0%, categorized as medium 22%, categorized as less than 71% and categorized as less than 7%. Therefore, it can be concluded that the average level of Physical Fitness of Students is in the category of Less and this result shows that the expected results have not been achieved.